Differences in Cognitive-Motor Interference in Older Adults While Walking and Performing a Visual-Verbal Stroop Task - Wollesen, Bettina; Voelcker-Rehage, Claudia (Frontiers in Aging Neuroscience, 2019)
Objectives: Studies using the dual-task (DT) paradigm to explain age-related performance decline due to cognitive-motor interference (CMI) which causes dual-task costs (DTC) revealed contradictory results for performances under DT conditions. This cross-sectional study analyzed whether differences in demographics, physical functioning, concerns of falling (CoF), and other mental factors can explain positive and negative DTCs in older adults while walking in DT situations. Methodology: N=222 participants (57-89 years) performed a single task (ST) and a DT walking condition (visual-verbal Stroop task) in randomized order on a treadmill. Gait parameters (step length, step width) were measured at a constant self-selected walking speed. Demographics (age, MMSE), physical functioning (hand grip strength), CoF (FES-I), and mental factors (SF-12) were assessed. An ANOVA revealed subgroup differences. A four-step hierarchical regression analysis was conducted identified variables determining DTC. Results: Three subgroups were identified: (1) participants (n=53) with positive DTCs (improvements under DT conditions), (2) participants with negative DTCs (n = 60) in all gait parameters, and (3) participants (n=109) who revealed non-uniform DTCs. Baseline characteristics between the subgroups showed differences in age (F(2,215)= 4.953; p < 0.01). The regression analysis revealed that physical functioning was associated with positive DTC and CoF with negative DTC. Conclusion: The results confirmed a huge inter-individual variability in older adults. They lead us to suggest that factors causing performance differences in DTCs needs to be reassessed. Functional age seems to determine DTCs rather than calendric age. Psychological variables particularly seem to negatively influence DT performance.